ANALYSIS OF THE BANKS ACTIVITIES ON THE FINANCIAL MARKET OF UKRAINE - FORKUN, Iryna; GORDEEVA, Tetyana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the activity of domestic banks in Ukraine’s financial market and examines the state and dynamics of the banking system’s assets, capital, and liabilities for 2020-2023. Ukraine’s financial market is experiencing significant challenges due to martial law, but these hard conditions also driving radical change and innovation in the sector. Due to the specificity of their activity, banks occupy a special place in the market economy and have a significant impact on the development of the financial market and the economy of the country. The integration of the national banking system into the world financial space is one of the leading directions of economic globalization, which strengthens the requirements for domestic banking institutions to increase their competitiveness and efficiency in providing financial services. This makes it necessary to study the essence and peculiarities of the functioning of banking institutions in the financial market of Ukraine in the modern, changing conditions of the development of economic relations between subjects of the national and international economy. The trend of consolidation of the banking system and withdrawal from the market of unreliable banks or banks whose capital belongs to under-sanctioned owners has been revealed. It was determined that despite the decrease in the number of these institutions, there was no significant deterioration of the main quantitative and qualitative indicators of the bank’s activity, which indicates the stability of the efficiency of their activity. The state, dynamics, and quality of the banking system’s credit portfolio were studied, and banks’ compliance with NBU prudential regulations regarding credit risk was analyzed. The consistently high value of 45% of the share of bank assets in GDP confirms the overall efficiency of these financial institutions. A positive thing is the reduction of NPL before the full-scale invasion, but with its onset, this indicator increased again. A characteristic feature of the activity of domestic banks at present is a significant increase in the interest of institutions in investments in securities, in particular, military government bonds, the share of investments in these securities in the total assets of banks is rapidly increasing. To stabilize the financial state of the country’s economy under the influence of "force majeure" circumstances, the banking system must constantly adapt its activities on the financial market, acting as an intermediary in the circulation of capital and financial resources